PENGARUH KEGIATAN KARANG TARUNA DALAM PENGAMALAN NILAI-NILAI PANCASILA SEBAGAI ETIKA BERBANGSA DAN BERNEGARA DI DESA SARI BAKTI KECAMATAN SEPUTIH BANYAK - Abdul Rozak; Hermi Yanzi; Edi Siswanto (Journal of Social Science Education, 2022)
This study aims to identify the influence of youth activities in the practice of Pancasila values as national and state ethics. The method used in this research is descriptive with a quantitative approach, and the number included in the population is 65 respondents, members of the taruna group. The sample used is a member of the youth organization which is then interpreted according to the data that has been presented. From the research results, it is known that the significance value (Sig.) of 0.000 is less than the probability of 0.05 and the thitung of 6.914 is greater than the ttabel of 0.2075. Then H1 and H0 accepted and is rejected. Thus, it can be concluded that there is an influence of youth activities in the practice of Pancasila values as national and state ethics in Sari Bakti village, Seputih Banyak sub-district. Keywords: Youth Organization, Pancasila, Youth Organization